(untitled) (Педагогіка вищої та середньої школи, 2008)
The given article exposes the specific of the use of the educational-supervisory programs, in particular at the study of graphic disciplines. Considered problems of introduction of the educational-supervisory programs in an educational process and credible ways of their decision.